The study of the phenomenology as one way of access for the improvement of the nursing assistance - Patrícia Campos Pavan Baptista; Miriam Aparecida Barbosa Merighi; Genival Fernandes de Freitas (Cultura de los Cuidados, 2012)
In the nursing, an increasing search for the research of qualitative nature, caused for the desire of the researchers in knowing the experiences of an illness not only is observed or determined events under the approach of the citizen and under the pathophysiological aspects. The present article is about an update study, in which if it intends to rescue the relevance of the study of the phenomenology for improvement in the quality of the assistance of nursing given to the customers, in view of whom our objective profession the satisfaction of the necessities basic human beings as well as the promotion of a care that exceeds the illness, and can articulate it the existence of the citizens.